Exploring Parents’ Experiences in Caring for Children with Chronic Illness: A Qualitative Study of Family-Centered Care - Pipin Cahyati; Muhammad Ihsan; Eka Sasmita (PT. Nasyah Medika Care, 2025)
Background: Caring for children with chronic illnesses requires parents to manage complex treatment demands, emotional uncertainty, changing family roles, and healthcare access barriers. Understanding these experiences is essential for developing culturally responsive family-centered pediatric care across diverse local communities. Research Objective: This study explored parents’ experiences in caring for children with chronic illnesses in Baubau, Southeast Sulawesi, from a family-centered care perspective. Methods: A qualitative descriptive study with a phenomenological approach involved 15 parents selected through purposive sampling. Data were collected through face-to-face, semi-structured, in-depth interviews and field notes. Interviews were transcribed verbatim and analyzed using Braun and Clarke’s six-stage thematic analysis. Trustworthiness was maintained through triangulation, member checking, peer debriefing, reflective notes, and an audit trail. Results: Five themes were identified: emotional adaptation from shock to acceptance; reorganization of family roles and daily routines; financial, geographical, and service-related barriers; inconsistent partnership with healthcare professionals; and resilience supported by spirituality and social relationships. Parents valued clear information, respectful communication, practical education, emotional support, and participation in treatment decisions. Referral outside Baubau increased transportation costs, income loss, and separation from other family members. Conclusion: Caring for children with chronic illnesses affects the entire family and requires sustained professional and social support. Healthcare facilities should strengthen culturally responsive family-centered care through shared decision-making, caregiver education, psychological and spiritual support, peer-support groups, and coordinated referral services.